The Polemic of the May 1998 Riots Against the Chinese Ethnicity - Vicki Dwi Purnomo; Andrie Irawan; Ishvi Joenaini Koenti (Journal of Legal and Cultural Analytics, 2023)
The May 1998 riots in Jakarta took place on 13-15 May 1998 which became history dark for Nation Indonesia, economic difficulties due to the crisis that occurred caused the community Indonesia experience difficulty fulfil need they. Consequence dissatisfaction on government Which No capable finish crisis bring up action demonstration by public Indonesia specifically from circles student. his death four student Trisakti make circumstances the more No under control with happening unrest in a number of place in Jakarta. The ethnic Chinese became one of the victims of the riots Where shop, House, nor Which identified as owned by person Chinese damaged and looted. which method used in this study is the historical research method. Technique collection data Which used is technique literature And technique documentation. The data analysis technique used is data analysis technique qualitative. Based on results study And discussion, take conclusion that ethnic Chinese background became victims of the Riots May 1998 in Jakarta are Entrepreneurs Chinese dominate economy and relation between Ruler Chinese with Ruler Order New.